IMPLEMENTASI PEMBERATAN PEMIDANAAN TERHADAP ANGGOTA TNI YANG MELAKUKAN TINDAK PIDANA ASUSILA - Alvaro David Gabriel Dumais; R. Rahaditya (UNES Law Review, 2023)
Criminal Sexual Violences or Sexual Violences, in fact, do not only occur in the midst of ordinary society, but also within active institutions of the Indonesian National Armed Forces (TNI). In this case it is clear that the TNI members involved have violated the soldier's oath and 8 (eight) TNI conscripts. In this case, every member who of course commits immoral crimes must be held responsible for their actions by receiving sanctions in the form of dismissal and appropriate punishment because they have damaged the good name of the TNI institution. The type of research method used in this writing is the normative legal research method. The method of normative legal research is carried out by studying documents and referring to studies of court decisions, principles, legal principles, legal theories, doctrines, and opinions of experts. The writing specification used is descriptive. It is used to explain various regulations and legal theories that can be correlated and examined in events or cases that occur in related problems by using secondary research data types and statutory approaches (statute approach). Therefore, it is hoped that the implementation of additional punishment in the form of dismissal can be given with the aim of providing a deterrent effect in order to maintain the image and reputation of the TNI.